Clinical and haematological parameters associated with patients of visceral leishmaniasis in a district of North Bihar - Saurabh, Kumar; Ranjan, Shilpi; Prasad, Rajeev Ranjan (International Journal Of Community Medicine And Public Health, 2017)
Background: Visceral leishmaniasis is highly endemic in West Champaran district of Bihar. This endemicity is supposed to be due to poor hygiene and sanitation and poor control of vectors. This study was done to study clinical and haematological parameters of Kala-azar patients in this area. Methods: A retrospective data collection was done in a medical college of north Bihar. Study duration was one year from January 2016 to December 2016. 43 cases, rk-39 positive from 13 blocks of W. Champaran admitted at medical college were studied for clinical and haematological parameters. Results: Bhitha was the highest affected block (25.58%) followed by Manjhaulia (23.25%) Fever was the commonest presentation whereas splenomegaly was the most common sign. Pallor was seen in 90 % cases and hepatomegaly in 60 % cases. Patients presented with bleeding manifestation in 9.3% cases and lymphadenopathy in 6.9% cases. Among blood parameters anaemia was seen in 93% cases and thrombocytopenia in 83%. Microcytic hypochromic blood picture was the most common peripheral blood picture. Conclusions: Extensive epidemiological investigation is needed to find out hidden cases in this area.